In-vivo stiffness assessment of distal femur fracture locked plating constructs. (July 2018) - Parks, Christopher; McAndrew, Christopher M.; Spraggs-Hughes, Amanda; Ricci, William M.; Silva, Matthew J.; Gardner, Michael J.
Abstract: Background: The purpose of this study was to design and validate a novel stiffness-measuring device using locked plating of distal femur fractures as a model. Methods: All patients underwent a laterally-based approach, with a bridging locked construct after indirect reduction. A custom and calibrated intraoperative stiffness device was applied and the stiffness of the construct was blindly recorded. Fourteen of twenty-seven patients enrolled with distal femur fractures (AO/OTA 33A and 33C) completed the study. Correlations between stiffness and callus formation, working length, working length/plate length ratio, number of distal locking screws, and fracture pattern were explored. Findings: Callus and modified radiographic union scale in tibias scores as a linear function of stiffness did not correlate (R2 = 0.06 and 0.07, respectively). Construct working length and working length to plate length ratio did not correlate to stiffness (R2 = 0.18 and 0.16 respectively). A combined delayed and nonunion rate was 14%. Lower extremity measure scores were not statistically different when comparing delayed and nonunion with healed fractures. Interpretation: The lack of correlation may have been due to the mechanical properties of the plate itself and its large contribution to the overall stiffness of the construct. To our knowledge, clinically relevant stiffness has not been described and this study may provide some estimates. This methodology and these preliminary findings may lay the groundwork for further investigations into this prevalent clinical problem. Other parameters not investigated may play a key role such as body mass index and bone mineral density. Level of evidence: Diagnostic/Prognostic Level II. Highlights: A custom device was used to measure stiffness of distal femur fixation constructs. This study provides estimates for in-vivo plate stiffness for fracture constructs. Nonunions remain a prevalent problem; this methodology warrants further study.